Glutathione: Chemistry and Biochemistry - Perjési, Pál (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
It has been known that cellular glutathione content and its speciation play a role, among others, in redox homeostasis, cell cycle control, immunological defense, and pathological abnormalities. Furthermore, it plays a significant role in the biotransformation of drugs and other endogenous or exogenous electrophilic species. Most of these cellular functions are related to the thiol function of the cysteine moiety.This reprint presents the publications that appeared in the Special Issue of Molecules, "Glutathione: Chemistry and Biochemistry." The first three contributions review the present-day knowledge of the GSH/GSSG system and the most important GSH-related proteins involved in regulating various cellular events. The subsequent four contributions present selected interventions that modulate the GSSG/2GSH system. One of the contributions to this session describes a new HPLC method to quantify the reduced and oxidized glutathione levels. The third session involves three contributions demonstrating the role of GSH in the metabolism of different candidate and clinically used anticancer drugs. One of the contributions, a theoretical work, provides helpful information for developing GSH analogs with high ACE inhibitor activity.By purpose and content, this Special Issue is addressed to the vast number of life science researchers (academic and industrial) and medical professionals who are interested in or already engaged in research that involves glutathione.